Pengembangan Media “Sijarwo” untuk Menunjang Pembelajaran Diferensiasi Mata Pelajaran IPA di Sekolah Dasar - Karima, Retmaniar (Jurnal Didaktika Pendidikan Dasar, 2024)
The development of digital learning media that integrates the belajar.id account and meets the learning styles and level of understanding of students is carried out because it is not yet available at SDN Sawahjoho 01. The aim of this research is to develop digital learning media that is feasible, practical and effective to support differentiated learning in elementary schools. This research method is Development Research with the ADDIE model which consists of 5 stages, namely Analysis, Design, Development, Implementation, Evaluation. The development product is called “SIJARWO" which is an acronym for Situs Belajar SD Sawahjoho. “SIJARWO” utilizes the Google Site feature which is integrated with the Belajar.id account and can be accessed using a smartphone or laptop connected to the internet network. The reseacrh results shows that “SIJARWO” media meets the very appropriate criteria with a material expert score of 3.37 and a media expert score of 3.50. Meanwhile, student responses obtained a score of 3.53 in the very practical category. Furthermore, the science learning outcomes of class VI students increased from an average pretest score of 68.29 to 88.24 in the posttest score with an n-gain score of 0.63 (medium category). It can be concluded that the development of “SIJARWO” media is very feasible, practical and effective so that it can support differentiated learning in science subjects in elementary schools.